Effect of Alley Width and Intra-Row Spacing of Subabool (Leucaena Leucocephala) on Soil Loss, Growth and Yield of Sorghum (Sorghum bico/or L. Moench) Under Rainfed Agro-Ecosystem - Haider, Ekhlaq; Gangwar, Munish; Bhatia, K.S. (Indian Journal of Agroforestry, 2020)
An experiment was carried out at Soil Conservation and Water Management Research Farm of C.S.Azad University of Agriculture and Technology, Kanpur during Kharif season of 1995-96. To study the effect of alley width and intra-row spacing of Leucaena on soil loss, growth and yield of sorghum. The results showed that initial and final plant populations of sorghum were unaffected due to alley width and intra-row spacing of Leucaena. Plant height of sorghum increased significantly with advancement of crop up to harvest due to alley width and also intra-row spacing of Leucaena leucocephala except at early stages of crop i.e.30 to 60 DAS. Plant girth increased significantly with increasing days after sowing due to alley width of Leucaena, where wider alley width produced healthier plants as compared to narrow alley width. Grain yield of sorghum significantly increased in wider alley width of 6.5 m while this was not affected significantly by intra-row spacing of Leucaena. Thus, alley width and intra-row spacing of Leucaena has left the impact on plant growth and phenological parameter of sorghum as well as on grain yield. The soil loss was significantly higher under wider alley width at 6.5 m as compared to narrow alley width of 4.5 m apart. However, intra-row spacing of 1.5 m exerts maximum soil loss 1.80 Uha while lowest 1.55 Uha was recorded at 0.5 m.